Literatur Review Perbandingan Metode Pengembangan Design thinking dengan Extreme Programming - Anggreni, Ni Komang Ayu Sri; Sastra, Nyoman Putra Putra; Wiharta, Dewa Made (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
With the development of applications, both through the web and mobile , applications cannot be separated from human-computer interaction. The ease of using the application is the target of developers to attract user s' interest. In this era of globalization, website applications and mobile platforms are the mostly used  for public branding. Application are used to deliver  message through visuals from the appearance of the application. This is inseparable from the User Interface and User Experience . In today pratice, UI/UX designers mostly favor attractive visuals over the essence and purpose of creating a website, creating deviaton at UI/UX theory, design element, and color. it is necessary to design a UI / UX in order to application is attractive and the purpose of making the application is in line with expectations. There are several approaches to application design, one of which is Design thinking and Extreme Programming . This research aims to compare the Design thinking approach with Extreme Programming where the test obtained based on a literature review concluded that Design thinking has advantages in approaching potential user s while Extreme Programming is less focused on potential user s.